A dialetic without synthesis: Georg Simmel’s contribution to Historical Sociology - Souza Jr, Robson Rocha (2020)
The objective of the analysis developed in this paper is to presente Simmel’s contribution to Historical Sociology throuhg three articulated efforts. Firstly, it is intended to distinguish its theoretical formulation from the two dominant traditions in Historical Sociology: the marxist tradition and the weberian tradition. Therefore, the first section is dedicated to a rapid presentation of how Marx and Weber conceive the historical course and its relation to social  structures. Afterwards, Simmel’s formulation is presented, highlighting the relation of the historical form with the temporal flow, conceived in the form of a dialectic without synthesis,  and the historical foundation of the social units. Finally, it is indicated how the formulation of Simmel finds parallel in the contribution of two contemporary sociologists: Abbott and  Sewell. At this point, highlighting the concept of turning point, formulated by Abbott and the complex articulation of a multiplicity of open and mutable structures, proposed by Sewell.